Bioremediation of Oil-Contaminated Soils Using Biosurfactants Produced by Bacteria of the Genus Nocardiopsis sp. - Liliya Biktasheva; Alexander Gordeev; Arina Usova; Anastasia Kirichenko; Polina Kuryntseva; Svetlana Selivanovskaya (Microbiology Research)
One of the effective and safe methods of soil cleanup from oil pollution is bioremediation by introducing microorganisms or their metabolites. In this study, the effect of biosurfactants produced by Nocardiopsis sp. 3mo on the rate of bioremediation of oil-contaminated soils was assessed. Biosurfactants were introduced into soils contaminated with 2% oil at a concentration of 0.05 and 0.1%, and the degree of hydrocarbon degradation was estimated within 63 days. It was found that the studied biosurfactant belonged to the glycopeptide type. The aeration and irrigation of oil-contaminated soil (PSA) resulted in a 5% decrease in the number of hydrocarbons. The introduction of biosurfactants into oil-contaminated soil at a concentration of 0.5 (BS(0.5)) and 1 g kg−1 (BS(1)) resulted in a 29 and 35% decrease in the content of hydrocarbons, respectively. The state of the soil microbiome was assessed by its metabolic activity. Thus, the respiratory activity of microorganisms on the first day after contamination increases by 5–7 times, and urease activity by 3–4 times. The introduction of oil into the soil during the first day reduces the activity of dehydrogenase by 2.3–1.6 times. In the process of bioremediation, the indicators of microbial activity returned to values close to the original. Thus, it was established that the use of biosurfactants produced by Nocardiopsis sp. 3mo increases the ability of the native soil community to degrade hydrocarbons.